2018
DOI: 10.1177/0954008318774837
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and temperature-dependent impedance spectroscopy of PVA/PEG polymer blend film

Abstract: In this work, polymer blend films based on polyvinyl alcohol (PVA)/poly(ethylene glycol) (PEG) were prepared by solution casting technique. X-ray diffraction (XRD) analysis was performed to investigate the structural details of the polymer blend. XRD pattern confirms the polycrystalline nature of the films. Sandwich structures of the type Ag-PVA/PEG-Ag were formed to study the dielectric and conduction properties in the frequency range 300 Hz–3 MHz and at different temperatures varying from 298 K to 420 K. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…From Figure i, it can be found that the shift in relaxation peaks toward higher frequency with an increase in the MWCNTs concentrations into PBCEs films. Although Figure ii shows temperature-dependent tan δ against a frequency (Hz) plot for the sample containing 10 wt % of MWCNTs which exhibits a frequency shift with temperature (from 30 to 100 °C) the relaxation peaks shift toward higher frequency regions. This shift in relaxation frequency may due to increased segmental motion of the polymeric chains.…”
Section: Resultsmentioning
confidence: 96%
“…From Figure i, it can be found that the shift in relaxation peaks toward higher frequency with an increase in the MWCNTs concentrations into PBCEs films. Although Figure ii shows temperature-dependent tan δ against a frequency (Hz) plot for the sample containing 10 wt % of MWCNTs which exhibits a frequency shift with temperature (from 30 to 100 °C) the relaxation peaks shift toward higher frequency regions. This shift in relaxation frequency may due to increased segmental motion of the polymeric chains.…”
Section: Resultsmentioning
confidence: 96%
“…Contrastingly, at higher frequencies, the direction of the electrical field changes too quickly to provide enough time for these charge carriers to accumulate and align themselves in the direction of the electrical field. This causes a decline in the dielectric constant, which ultimately increases the conductivity [77][78][79]. Hence, the impedance spectra suggested that as the proportion of COS increased beyond 2.50 wt% (CP1), the conductivity of the PVA/COS films (CP2-CP4) reduced considerably.…”
Section: Impedance Spectroscopy Analysismentioning
confidence: 99%
“…[ 20 ] Xin et al [ 30 ] used PEG and zinc nanoparticles to prepare lubricants, and the solution could form a better lubricant film during the lubrication process, hence reducing frictional wear. PVA, as an organic polymer, has good film‐forming properties [ 31 ] and is a preferred material for the preparation of composite materials, which is often used for artificial joint lubrication and preparing composite films with other polymers. [ 32–35 ] Chen et al [ 36 ] prepared a high‐strength, low‐friction PVA–HA/PAA composite hydrogel and showed a strengthening and toughening effect.…”
Section: Introductionmentioning
confidence: 99%